Healthy Elderly in Pandemic: Physical Activities During The Covid-19 Pandemic - Angkit Kinasih; Theresia P.E Sanubari; Hidayat Hidayat (STIKes Hang Tuah Pekanbaru, 2021)
The elderly experience a decline in health due to decreased body functions caused by increasing age. Covid-19 has spread since March 2020 has led to the emergence of restrictions on activities, namely PSBB. These conditions lead to various changes related to efforts to overcome health problems. The purpose of this study is to explore physical activity by paying attention to social and environmental conditions during the Covid-19 pandemic in the elderly in Kebumen Village, Banyubiru District. The research used a descriptive qualitative research method. The data used structured interviews with 4 elderly people in Banyubiru District, Kebumen Village who were disabled at the Banyubiru Health Center. The participants involved elderly with inclusion criteria of women aged 55 - 61 years, physically and mentally healthy, often doing physical activities, domiciled in Kebumen Village, Banyubiru District. The study was conducted in February - July 2020 in Kebumen Village, Kebumen Village, Banyubiru District, Semarang Regency. The results showed that most of the participants experienced changes in physical activity due to the PSBB. The elderly must adapt to conditions during a pandemic that causes a reduction in the quality and quantity of physical, social, and environmental activities. Gathering activities that are not useful are not carried out by the elderly group even though they are useful for maintaining their health.